Pulmonary Hypertension: Scientometric Analysis and Density-Equalizing Mapping. - Michael Götting; Mario Schwarzer; Alexander Gerber; Doris Klingelhöfer; David A Groneberg (PLoS ONE)
Pulmonary hypertension (PH) is characterized by the increase of the mean pulmonary arterial pressure in the lung circulation. Despite the large number of experimental and clinical studies conducted on pulmonary hypertension, there is no comprehensive work that analyzed the global research activity on PH so far. We retrieved the bibliometric data of the publications on pulmonary hypertension for two periods from the Web of science database. Here, we set the first investigation period from 1900 to 2007 (t1) due to the cited half life of articles and the relating difficulties to interpret the citation parameters. The second evaluation period (t2) covers the time interval from 2008 onwards including the year 2015. The data were analyzed and processed to density-equalizing maps using the NewQIS platform. A total number of 18,986 publications were identified in t1 that come from 85 countries. The US published the highest number of publications (n = 7,290), followed by the UK, Germany, Japan and France. In t2 19,676 items could be found worked out by 130 countries. The raking started just the same with the USA as most publishing nation with 7,127 publications on PH, followed by the UK and Germany. Japan fell back on 6th place, whereas China came into view on the 5th position. Analyzing the average citation rate as a parameter for research quality, Mexico reached the highest value in t1 and Ireland in t2. While, the country specific h-index underlined the leading position of the US research in both evaluation periods again. The average number of international collaboration items was expanding from none in 1978 to 530 items in 2015 with the USA as the country with the highest number of collaboration articles. The present study is the first large scale density-equalizing mapping and scientometric analysis of global PH research activity. Our data draw a sketch of the global research architecture in this field, indicating a need for specific research programs in countries with a lower human development index.